2019
DOI: 10.1155/2019/1059369
|View full text |Cite
|
Sign up to set email alerts
|

Less Experienced Telestroke Consultants Are More Likely to Go On-Camera, but Less Likely to Give tPA

Abstract: Background Stroke telemedicine (telestroke) increases tPA availability and administration. However, the effective use of telestroke requires training, which is not a standard component of vascular neurology training. As a result, many providers learn telestroke skills “on the job” after finishing their training. Aims We sought to explore if providers with more telestroke experience would be more efficient in the utilization of telemedicine, compared to providers with less experience. Methods We prospectively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…7 Data from the University of Utah linked training and experience with more appropriate deployment of teleconsultations and avoidance of unnecessary utilization. 8 Familiarity and repetition can clearly improve teleneurology competency and efficiency.…”
Section: Existing Models Of Teleneurology Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Data from the University of Utah linked training and experience with more appropriate deployment of teleconsultations and avoidance of unnecessary utilization. 8 Familiarity and repetition can clearly improve teleneurology competency and efficiency.…”
Section: Existing Models Of Teleneurology Trainingmentioning
confidence: 99%
“…The AAN recognized the need to incorporate telemedicine in neurology training in 2013 and multiple subsequent publications outline recommended curricula, 1,5,6,9 provide data on implemented programs, 7,9,10 and demonstrate the real-world benefits of systematic telemedicine training. [7][8][9] Anecdotally, the residents at our 3 institutions have expressed increasing interest and curiosity regarding additional teleneurology exposure, which is magnified by the emergent changes in clinical practice implemented in response to the COVID-19 pandemic. The lack of mandated education in this area has led to slow adoption of training in teleneurology.…”
Section: Existing Models Of Teleneurology Trainingmentioning
confidence: 99%
“…This paper also builds on a 2012 review, 20 which found that relationships (e.g., between hubs and their spoke sites) matter more than technology sophistication, by showing one kind of relationship that works well. To address a known lack of formal training for acute telestroke, 45…”
Section: Integration With Previous Workmentioning
confidence: 99%
“…This paper also builds on a 2012 review, 21 which found that relationships (e.g., between hubs and their spoke sites) matter more than technology sophistication, by showing one kind of relationship that works well. To address a known lack of formal training for acute telestroke, 48 Last, our study adds to research on physicians' increasing use of secure, consumer-oriented mobile messaging software like WhatsApp. 49,50 In our study, mobile messaging was associated with team cohesion by fostering participant satisfaction and ease of communication.…”
Section: Integration With Previous Workmentioning
confidence: 99%
“…This paper also builds on a 2012 review, 21 which found that relationships (e.g., between hubs and their spoke sites) matter more than technology sophistication, by showing one kind of relationship that works well. To address a known lack of formal training for acute telestroke, 48 our study shows how NTSP's weekly calls, discussions of the latest evidence, and open communication between peers and program administrators link specialists in different career stages for on-the-job training.…”
Section: Integration With Previous Workmentioning
confidence: 99%